Vowel and Consonant Phoneme Changes in Reading Arabic Texts by Students of MAN 3 Mandailing Natal: An Autosegmental Phonology Analysis - Rahlina Muskar; Khairina Nasution; Fatimatuzzahra Fatimatuzzahra; Rafiqa Ulfah (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2025)
The research was qualitative research using generative linguistic method. This study is aimed at analyzing the changes of sound vocal and consonants in the read Arabic text by students from school MAN 3 Mandailing Natal from the aspect of phonological auto segmental. The data are from the recording of the read Arabic text words wich contain the sounds of vocal [a] and plosive consonants ض   [ɖ],  ط [ʈ] and ق [q[.Data from there 40 informants (20 males and 20 females ) of the research are the secondary school students from school MAN 3 Mandailing Natal. Data from the study are analyzed theoretically based on the phonological auto segmental, Sagey`s representation of distinctive features model (1986), Clements and Keyser`s representasion of syllable tiers (1983). In the recitation of Arabic text by students from MAN 3 Mandailing Natal readers the Arabic text vocal and consonants experiences a substitution of vocal and consonant by the closest. Vocal and consonant, that is vocal [a] which substituted with vocal [ɔ] and coronal plosive consonants ض  [ɖ],ط [ʈ] and ق [q[  which are substituted with coronal plosive consonants [d, t, k]. The substitution of vocal and consonant recitation the Arabic text by reciters of students from school MAN 3 Mandailing Natal has resulted the phonological changes in Arabic language and the meaning of Arabic words.